Status of Serpent Monte Carlo code in 2024 - Leppänen Jaakko; Valtavirta Ville; Rintala Antti; Tuominen Riku (EPJ Nuclear Sciences & Technologies)
The Serpent Monte Carlo code has been in public distribution for 15 years, and has a large international user basis with both research and commercial applications. Serpent is currently developed as part of the Kraken multi-physics framework, which has dedicated capabilities for core-level reactor physics analyses. In Kraken, Serpent can be used either as a high-fidelity neutronics solver, or for generating homogenized group constants for the Ants nodal neutronics code. The neutron and photon transport modes in Serpent enable using the code also for various stand-alone applications beyond reactor physics, such as radiation shielding and fusion neutronics. This paper presents a review of the current status and capabilities of Serpent, corresponding to the latest release 2.2.1. The main features are introduced, with references to publications with more detailed methodological descriptions.